Alternative splicing‐regulated protein of hepatitis B virus hacks the TNF‐α‐stimulated signaling pathways and limits the extent of liver inflammation. Issue 5 (28th January 2015) - Pol, Jonathan G.; Lekbaby, Bouchra; Redelsperger, François; Klamer, Sofieke; Mandouri, Yassmina; Ahodantin, James; Bieche, Ivan; Lefevre, Marine; Souque, Philippe; Charneau, Pierre; Gadessaud, Noémie; Kremsdorf, Dina; et al.
ABSTRACT: Hepatitis B splicing‐regulated protein (HBSP) of the hepatitis B virus (HBV) was uncovered a few years ago but its function remains unknown. HBSP expression occurs from a spliced viral transcript that increases during the course of liver disease. This study aimed at characterizing the impact of HBSP on cellular signaling pathways in vitro and on liver pathogenesis in transgenic (Tg) mice. By RT‐qPCR array, NF‐κB‐inducible genes appeared modulated in HepG2 cells transduced with a HBSP‐encoding lentivirus. Using luciferase and Western blot assays, we observed a decreased activation of the NF‐κB pathway in HBSP‐expressing cells following TNF‐α treatment, as illustrated by lower levels of phosphorylated IκB‐α. Meanwhile, the level of phosphorylated JNK increased together with the sensitivity to apoptosis. The contrasting effects on JNK and IκB‐a activation upon TNF‐α stimulation matched with a modulated maturation of TGF‐β‐activated kinase 1 (TAK1) kinase, assessed by 2‐dimensional SDS‐PAGE. Inhibition of the NF‐κB pathway by HBSP was confirmed in the liver of HBSP Tg mice and associated with a significant decrease of chemically induced chronic liver inflammation, as assessed by immunohistochemistry. In conclusion, HBSP contributes to limit hepatic inflammation during chronic liver disease and may favor HBV persistence by evading immune response.—Pol, J. G., Lekbaby, B., Redelsperger, F., Klamer, S., Mandouri, Y., Ahodantin, J., Bieche, I., Lefevre, M., Souque, P., Charneau, P., Gadessaud, N., Kremsdorf, D., Soussan, P. Alternative splicing‐regulated protein of hepatitis B virus hacks the TNF‐α‐stimulated signaling pathways and limits the extent of liver inflammation. FASEB J. 29, 1879‐1889 (2015). www.fasebj.org